Identifying Privilege and White Fragility - Miller, Brennan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2016)
The purpose of this activity is to give students a better understanding of racial privilege by having them identify "White Fragility"— when the least amount of racial stress provokes emotional and behavioral defensive moves, such as anger or evasion. This activity assesses students’ comprehension of White Fragility and students’ ability to understand the impacts of privilege on understanding race relations. In Part I, students review group privilege and White Fragility through an instructor guided class discussion. In Part II, students form groups to complete a handout. Students use the handout to match ten triggers of racial stress to potential responses to such triggers. Finally, Part III has students write a critical reflection paper about the activity.